2019
DOI: 10.1186/s12887-019-1628-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk of urinary tract infection in malnourished children: a systematic review and meta-analysis

Abstract: Background There are vast differences in prevalence rates of urinary tract infection (UTI) reported among malnourished children globally. We conducted a systematic review and meta-analysis to provide estimates of pooled prevalence of UTI among these children and combined UTI risk in comparison with their well-nourished counterparts. Methods We systematically searched electronic databases (MEDLINE, EMBASE, ISI Web of Science and African Journals Online; date of the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Approximately 25% of children younger than 5 years of age show a malnourished state in developing countries [ 2 ]. Malnutrition remains an important risk factor for predisposition to respiratory and intestinal infections [ 3 , 4 , 5 , 6 ]. Protein energy malnutrition (PEM) is also an immunodeficiency that is strongly associated with susceptibility to infections [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 25% of children younger than 5 years of age show a malnourished state in developing countries [ 2 ]. Malnutrition remains an important risk factor for predisposition to respiratory and intestinal infections [ 3 , 4 , 5 , 6 ]. Protein energy malnutrition (PEM) is also an immunodeficiency that is strongly associated with susceptibility to infections [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…tethered cord syndrome, meningitis, hypoxic ischemic encephalopathy, invisible spina bi da) and urodynamic change were risk factors for ESBL-UTI is still unknown. Studies also reported that the prevalence of UTI and ESBL (+) UTI was higher in malnourished children [13,14] . Whether undernourishment was independent risk factors for ESBL positive UTI is also unclear.…”
Section: Discussionmentioning
confidence: 95%
“…In a systematic review and meta-analysis, 26 cross-sectional and 8 case-control studies reporting on UTI prevalence in malnourished children was included, and they found that UTI is more prevalent in malnourished children than in their well-nourished counterparts [13] . Another study included 402 malnourished children in Tanzania and data showed that more than 37 % of UTI isolates were exhibiting extended spectrum beta lactamase (ESBL) phenotype [14] .…”
mentioning
confidence: 99%
“…The risk of UTIs was U-shaped in certain age groups, suggesting that both underweight and obesity predispose children to UTIs. In a recent meta-analysis involving 3,294 malnourished children, the pooled odds ratio for UTIs was 2.34 with respect to malnutrition, and the risk of UTIs increased with the severity of malnutrition [ 14 ]. In a systematic review of children aged 6-59 months, UTIs were found in 24.1% of severely malnourished children [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of childhood obesity has been increasing, and that of childhood underweight still remains high [ 12 , 13 ]. Although associations between the weight status of children and UTI prevalence have been documented in the severely underweight or obese individual category [ 5 , 14 , 15 ], to the best of our knowledge, no comparable analysis has yet explored the associations of UTI incidence with a comprehensive set of BMI categories, ranging from underweight to obese, among children. Population-based epidemiology studies regarding UTIs in children are also unavailable in Korea, although a few retrospective population-based studies have been published based on epidemiological data on UTIs in other countries [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%